The influence of mobile instant messaging in language education: perceptions of current and future teachers. - Cremades-García, Raúl; Onieva-López, Juan Lucas; Maqueda-Cuenca, Eugenio; Ramírez Leiton, John Jairo (Taylor&Francis, 2019)
The globalisation of mobile instant messaging (MIM) in applications like WhatsApp encourages the use of a non-standard linguistic register. The purpose of this study is to determine and assess the perception of school teachers and teaching students on this issue in relation to the language education. This descriptive transectional study has been carried out with a non-probabilistic sample of 652 people, of whom 321 are active teachers at public schools (Infant, Elementary and Secondary School) in the province of Málaga (Spain), and 331 are students of the four courses in Primary Education at the University of Málaga. The data were collected through an own questionnaire, validated through a pilot test of the instrument, which yielded both qualitative and quantitative information. The results show no significant differences between the perceptions of teachers and students regarding the influence of MIM on the increasingly less normative linguistic uses of school-age children. Finally, the conclusion discusses the benefits and difficulties of the use of this kind of app in the classroom. Both groups agree on the need to work with this issue outside of school and to use instant messaging as a resource to improve language education.
This is an Accepted Manuscript of an article published by Taylor & Francis in INTERACTIVE LEARNING ENVIRONMENTS on 2021, available at: https://doi.org/10.1080/10494820.2019.1612451 Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/5360 (Accepted Version [pathway a])
Keywords: Lengua materna - Estudio y enseñanza - Efectos de las innovaciones tecnológicas; Mobile instant messaging (MIM); Mobile communication; WhatsApp; Virtual environments; Digital writing; Language education; Teacher training; Normative grammar